Enantioselective Functionalization of Radical Intermediates in Redox Catalysis: Copper-Catalyzed Asymmetric Oxytrifluoromethylation of Alkenes() - Zhu, Rong (2013)
[Image: see text] A method for the efficient enantioselective oxytrifluoromethylation of alkenes has been developed using a copper catalyst system. Mechanistic studies are consistent with a metal-catalyzed redox radical addition mechanism, in which a C–O bond is formed via the copper-mediated enantioselective trapping of a prochiral alkyl radical intermediate derived from the initial trifluoromethyl radical addition.